2018
DOI: 10.1021/jacs.8b08464
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adventitious Carbon in Photo-catalytic Nitrogen Fixation by Titania

Abstract: Photo-catalytic fixation of nitrogen by titania catalysts at ambient conditions has been reported for decades, yet the active site capable of adsorbing an inert N 2 molecule at ambient pressure and the mechanism of dissociating the strong dinitrogen triple bond at room temperature remain unknown. In this work in situ nearambient-pressure X-ray photo-electron spectroscopy and density functional theory calculations are used to probe the active state of the rutile (110) surface. The experimental results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 34 publications
3
101
0
Order By: Relevance
“…Among them, Mo 2 C and W 2 C showed the best catalytic activity due to the large electron transfer during the step of hydrogenation, suggesting that the beneficial design of Mxene cocatalysts has a significant meaning for synthesizing novel catalysts for nitrogen reduction. Over again, Benjamin and his group recently combined theoretical DFT calculation and preliminary experimental results to support their hypothesis that surface‐bound carbon radicals (C*) and other carbon‐based sites selectively assist the reduction of nitrogen at ambient condition ( Figure b) . Overall, there is no doubt that cooperation of cocatalyst enables the promotion of photo(electro)catalytic nitrogen fixation.…”
Section: Advanced Photo(electro)catalysts and Structure Engineeringmentioning
confidence: 96%
See 1 more Smart Citation
“…Among them, Mo 2 C and W 2 C showed the best catalytic activity due to the large electron transfer during the step of hydrogenation, suggesting that the beneficial design of Mxene cocatalysts has a significant meaning for synthesizing novel catalysts for nitrogen reduction. Over again, Benjamin and his group recently combined theoretical DFT calculation and preliminary experimental results to support their hypothesis that surface‐bound carbon radicals (C*) and other carbon‐based sites selectively assist the reduction of nitrogen at ambient condition ( Figure b) . Overall, there is no doubt that cooperation of cocatalyst enables the promotion of photo(electro)catalytic nitrogen fixation.…”
Section: Advanced Photo(electro)catalysts and Structure Engineeringmentioning
confidence: 96%
“…b) Thermodynamic cycle of N 2 reduction on a carbon substitution at bridging oxygen. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Advanced Photo(electro)catalysts and Structure Engineeringmentioning
confidence: 99%
“…Inspiration from enzymes and homogeneous systems demonstrate the potential to design complex active sites to improve catalyst performance at ambient conditions [181]. In situ characterization techniques, such as attenuated total reflectance-FTIR, SEIRAS, and in situ near ambient-pressure X-ray photo-electron spectroscopy, can detect reaction intermediates or active sites [81,182]. Along with DFT simulations, the reaction mechanism and screen principles would be reasonably deduced [183].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the recent finding that carbon surface species interact strongly with nitrogen. [30] Another issue is surface reconstruction on adsorption, where the adsorbate-adsorbate interaction is mediated by changes in both the electronic and atomic structure of the surface. The most common reconstruction observed was a substantial shift of Ti atom and sub-surface oxygen toward the surface.…”
Section: Prediction Of Adsorption Energiesmentioning
confidence: 99%
“…[28] Theoretical calculations also demonstrated that the halfmonolayer coverage of NO on the TiO 2 (110) is in agreement with the experimental results. [29] Moreover, recent work by Comer et al found that carbon species on TiO 2 may interact strongly with N 2 and other nitrogen-containing species, [30] suggesting that high and mixed adsorbate coverages are particularly relevant for nitrogen chemistry on TiO 2 . Therefore, accounting for lateral adsorbate-adsorbate interactions and mixed coverages is critical to gaining a detailed understanding of the stability different terminations for TiO 2 and other oxides and transition-metal compounds under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%